APPLICATION OF A PROBLEM BASED LEARNING (PBL) LEARNING MODEL ORIENTED BY LOCAL WISDOM TO THE CRITICAL THINKING ABILITY OF CLASS V PRIMARY SCHOOL STUDENTS - Baltasar Tiga Raja; Julhidayat Muhsam (Mimbar PGSD Flobamorata, 2023)
The aim of this research is to describe the application of the Problem Based Learning (PBL) learning model oriented to local wisdom on students' critical thinking abilities. This type of research is Classroom Action Research (PTK). The subjects of this research were class V students of SDK Sta. Maria Assumpta, numbering 31 students. Data collection techniques use written tests and observation. This research instrument uses story questions, worksheets, interviews, questionnaires and observations. The data analysis used is quantitative descriptive analysis. The results of the research show that the use of the Problem Based Learning learning model can improve critical thinking skills and learning outcomes in solving post-test questions after following lessons in the Pancasil and Citizenship Education class V SDK Sta. Maria Assumpta. This can be proven by the increase in students' critical thinking abilities from the initial condition with an average (pre-cycle) of 57.58 to 53.87 and in the second cycle it increased significantly with a value of 82.96. In this condition, there was also progress in increasing students who achieved the success criteria, increasing from 25.80% pre-action, 32.26% in cycle I and 92.59 in cycle II.